The upside of down why the rise of the rest is good for the West - Kenny, Charles (Basic Books, 2013)
America is in decline, and the rise of the East suggests a bleak future for the world's only superpower: so goes the conventional wisdom. But what if the traditional measures of national status are no longer as important as they once were? What if America's well-being was assessed according to entirely different factors?